Scientific analysis of organization intellectual capital using categorical grid method (Nexo Revista Científica, 2022)
The article proposes the author's scientific approach using the categorical grid method to determine the essence and composition of an organization's intellectual capital elements. They determined the list of elements describing the problem field of research. A categorical network has been formed that determines the scenarios for interacting intellectual capital elements. Possible connections between the tops of the triadic grid of intellectual capital phenomenon are revealed, which makes it possible to clarify the elemental composition of intellectual capital, to correlate the concepts of "consumer capital", "client capital", and "relational capital". The performed interpretation of the developed model of the triadic grid makes it possible to comprehend and describe the behavior of intellectual capital and possible scenarios for its development.